Modular Defenses with Tires, Geomesh, and Vetiver for Water Erosion Control in the Cahuachulla Stream – Combapata 2025 - Zecenarro Choque, Richard Ariel; Quispe Ccanchi, Adalid Rosmel; Urbiola, Alfredo Mamani; Cutipa, Ambrocio Mamani (International Journal of Aquatic Research and Environmental Studies, 2026)
This research develops a methodology for the design and construction of modular defenses using recycled tires, geogrids, and Chrysopogon zizanioides (vetiver) to control hydraulic erosion in the Cahuachulla stream basin, Peru. The study evaluates the structural effectiveness of tire-geogrid modules as an eco-friendly alternative to traditional gravity walls. The methodology integrates bioengineering principles to stabilize slopes and reduce sediment transport. Results indicate that the modular system significantly improves soil retention and energy dissipation of water flow. The proposal offers a sustainable, low-cost solution for disaster risk management in Andean basins, demonstrating that recycled materials combined with vegetation effectively mitigate land degradation and prevent landslides.